Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Prestasi Belajar Matematika pada Siswa Kelas V Sekolah Dasar - Intan Tri Septiana; Okto Wijayanti; Arifin Muslim (Universitas PGRI Semarang, 2019)
The background of this reseach was the low learning achievement of the students in mathematic subject at the fifth grade in elementary school. The aim of the study was enhancing the mathematic learning achievement in a learning material of data presentation through Problem Based Learning (PBL) model. The subject of this reseach was the fifth grade students that was 22 students, which 11 of them were male and 11 others were female. This researchused classroom action reseach design which was proposed by Kemmis and Taggart. This reseach was done in two cycles. Each cycle involved two meetings,which took 2 x 35 minutes. The instruments to collect the data were test and non-test. The result showed that the steps to implement Problem Based Learning (PBL) model were: (1) orienting the problem, (2) organizing students to learn, (3) guiding students (individual and group) to conduct investigation, (4) presenting the result or discussion, (5) analyzing and evaluating the problem solving. Based on the observation on the learning process both on cycle I and on cycle II, the data showed that the students’ mathematic achievement in the data presentation material was improved. The percentage on the cycle I was 43.75%, which gets enough criteria and on the cycle II was 86,36%, which gets very good criteria. The percentage of students’ learning achievement has achieved the indicator of success that has been determined, which was 80%. This leads to the conclusion that the implementation of problem based learning (PBL) model was able to enhance the mathematic learning achievement in a learning material of data presentationat the fifth grade in elementary school.